Effect of Postoperative Immobilization Method on Outcomes Following Triangular Fibrocartilage Complex Transosseous Foveal Repair: Long-Arm Cast Versus Muenster Brace - Oh, Hyun-Cheol; Kim, Hyoung Bok; Kang, Hyun Tak; Lee, Youngwoo; Lee, Jun-Ku (Clinics in orthopedic surgery, 2025)
Background: The optimal postoperative immobilization method following triangular fibrocartilage complex (TFCC) foveal repair remains debated. While long-arm casting effectively restricts wrist rotation, it also limits elbow movement and may cause discomfort. The Muenster brace, which allows partial elbow flexion while restricting wrist rotation, has been proposed as an alternative. This study compared clinical outcomes, patient satisfaction, and complication rates between long-arm cast (LAC) and Muenster brace immobilization. Methods: A retrospective comparative study was conducted on 40 cases from 37 patients who underwent TFCC transosseous foveal repair between March 2021 and February 2024. Patients were categorized into 2 groups: the LAC group (n = 19) and the Muenster brace group (n = 21). Demographics, radiologic assessments, operative details, and pre- and postoperative functional outcomes were analyzed. Pain and function were assessed using a visual analog scale (VAS) and the Disabilities of the Arm, Shoulder and Hand (DASH) score. Patient satisfaction and complications were recorded. Results: The mean patient age was 29 years, with an average follow-up of 282 days. Preoperative VAS scores (6.3 ± 1.9) improved to 1.2 ± 1.4, and DASH scores improved from 52.6 ± 16.0 to 10.4 ± 12.4. No significant differences were found between groups in demographics, tear classification, operative time, or preoperative functional scores. Postoperative pain relief, functional improvement, grip strength, and satisfaction were comparable. Minor complications included 1 case of transient cubital tunnel syndrome and 1 case of persistent pain requiring revision in the LAC group. In the Muenster group, 1 patient sustained a traumatic re-injury, and another developed distal radioulnar joint instability. No infections, tendon ruptures, or severe stiffness occurred. Conclusions: Both immobilization methods yielded comparable outcomes and satisfaction. While the Muenster brace improves elbow mobility, its effectiveness in preventing retears was similar to that of LAC. KCI Citation Count: 0